Economic Institutional Empowerment Model as A Climate and Energy-Independent Village Based on Local Wisdom - Elli WIDIA; Chablullah WIBISONO (International Journal of Environmental, Sustainability, and Social Science, 2024)
Village development from the perspective of community empowerment is to increase community participation in institutions by utilizing economic potential resources and local wisdom. The purpose of the research is to analyze and design a model of economic institutional empowerment at the location of Sambak Village, Kajoran Subdistrict, Magelang Regency, Central Java Province as a productive and innovative village that was awarded the Climate Village and Independent Innovation Champion. The research used a qualitative method with Participatory Rural Appraisal (PRA) which is relevant for constructing reality through observation, dialogical interviews, documentation, and Focus Group Discussion (FGD). Research informants were selected purposively, namely administrators and members of Micro, Small, and Medium Enterprises (MSME’s) and Village-Owned Enterprises (VOE), village government, and empowerment activists. PRA research analysis obtains data construction, reduction, and categorization which can then design empowerment programs or models. The results showed that Village governments need to create and run economic institutional empowerment programs in partnership with educational institutions and empowerment activists so that VOEs and MSME’s become integrated institutions. The empowerment programs needed are institutional management, administration, finance, promotion as well as digital marketing. Sambak Village can become a model and destination for an energy-independent productive and innovative Eduwisata.